Kepentingan Negara dalam Peacekeeping Operations PBB di Darfur tahun 2008-2017 - Nindya Kartika Sari; Reni Windiani (Journal of International Relations Diponegoro, 2018)
The conflict in Darfur broke out in 2003 which was accompanied by a series of crimes against humanity that threatened civilians in Darfur, in 2007 the UN passed a resolution containing a deployment of the UN's hybrid peacekeeping mission join forces with the African Union called UNAMID, which until 2017 UNAMID failed in carrying out its mission. This study aims to analyze the causes of Peacekeeping Operations failures in Darfur in the range of 2008-2017, this research uses Realism theory to explain the concept of state interests that are the cause of failure in Peacekeeping Operations in Darfur, the results of this study indicate UNAMID's failures caused by the UN's lack of political will and the lack of attention from UN Security Council member countries such as the US, UK, and France in imposing strict sanctions and policies on Sudan as perpetrators of humanitarian crimes in Darfur, the results also indicate the interests of other UNSC members as the reason of failure in UNAMID, namely Russia and China which support the government of Sudan and they often sabotaged the peace mission process in Darfur, which the UN does not take firm action against.